Empirics of Tourism-Led Growth in India, 1995 to 2016 - ROUT, Himanshu B.; MISHRA, P. K.; PRADHAN, B. B. (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).08, 2019)
In the globalized world, the travel and tourism have been considered crucial for achieving inclusive growth, especially in less developed economies. It has been increasingly recognised as a good contributor to national income and employment. So it can be used an instrument for achieving a higher rate of economic growth of a country in the long-run. In this line of argument, this paper examined the causal relationship between tourism and economic growth in the context of Indian States/UTs in a panel data framework. The empirical findings support the tourism-led growth hypothesis in the long-run and growth-led tourism hypothesis in the short-run. Thus, the policy choice is to make the tourism instrumental, through its promotional strategies, for the inclusive and sustainable development of India.